Penetration resistance and mechanical properties of graphene oxide/epoxy resin—A molecular dynamics investigation. Issue 7 (21st April 2021) - Ren, Sixi; Yang, Qingsheng; Shang, Junjun
Abstract: The penetration of salt solution into graphene oxide/epoxy resin (GO/EP) will cause structural damage, decrease in mechanical properties, and reduce service life. In this study, molecular dynamics method was used to simulate the penetration of the 3.5% NaCl solution through the GO/EP. In order to understand the effect of GO surface functional groups on the barrier properties of the GO/EP, a pure graphene model and three kinds of GO models modified with oxygen‐containing functional groups (ether, hydroxyl, and carboxyl) were established, respectively. The penetration resistance of GO/EP was analyzed. The type of oxygen‐containing functional group affects the penetration rate of the salt solution and the GO/EP interface performance. The spatial distribution and kinetic behavior of the salt solution were studied. The results show that the salt solution molecules trapped in GO/EP were mainly concentrated at the interface between GO and EP, which is the main reason for the degradation of the GO/EP interface performance. Affected by GO, the penetration process of ions can be divided into multiple stages, and its motion state was different depending on the type of functional group. Abstract :